Ø¢Ø±Ø§Ø¡ Ø§Ø¨Ù† Ù‚ÙŠÙ… Ø§Ù„Ø¬ÙˆØ²ÙŠØ© Ø§Ù„Ù†ØÙˆÙŠØ© Ø§Ù„Ù…Ø®ØªÙ„ÙØ© Ù…Ø¹ Ø¬Ù…Ù‡ÙˆØ± Ø§Ù„Ù†ØØ§Ø© ÙÙŠ ØªÙØ³ÙŠØ± Ø§Ù„Ø¢ÙŠØ© Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ© - Thohirin, Thohirin (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
Imam Ibn Qoyyim better known as 'Ulama' experts Fiqh, Tafsir and Hadith apparently also had a stake in the science, as evidenced by the books he authored were close relation with Linguistics as the book Miftah dar al-Sa'adah more- more books Badai'ul al-Fawaid. Its contents are more specific deal about rules Nahwu and shorf and linked to interpret the text of the holy verses of the Koran. Therefore, the authors are interested in investigating. In this paper the authors formulate the problem as follows: 1. What do nahwu Ibn Qoyyim in interpreting the verses of the Koran? 2. Where heeling Ibn Qoyyim in nahwunya opinion ?. The method used by writer is descriptive method. The author describes the majority opinion of experts nahwu compared with the opinion of Ibn Qoyyim in interpreting the Koran. Ibn Qoyyim opinion in interpreting the Koran is a textual schools. While heeling Qoyyim to his teacher Ibn Ibn Taymiyya whose expertise in the field of hadith scholars and Hanbali schools.